Relevance of Dr. B.R. Ambedkar for inclusive development in India : inclusive development, women empowerment and social justice - National Conference on "Relevance of Dr. B.R. Ambedkar for Inclusive Development in India" (2016 : Santiniketan, India); Pal, Sukumar; Visva-Bharati. SC, ST and OBC Employees' Association; Visva-Bharati (New Delhi : New Delhi Publishers, 2017)
Contibuted articles presented at National Conference on "Relevance of Dr. B.R. Ambedkar for Inclusive Development in India", organized by SC, ST and OBC Employees' Welfare Association of Visva-Bharati on April 14, 2016 at Visva-Bharati, Santiniketan, India.
Includes bibliographical references.
Keywords: Ambedkar, B. R. -- 1891-1956 -- Political and social views -- Congresses; Ambedkar, B. R. -- 1891-1956 -- Philosophy -- Congresses; Marginality, Social -- India -- Congresses; Social integration -- India -- Congresses; Social justice -- India -- Congresses; India -- Social conditions -- Congresses; India -- Social policy -- Congresses